Toxic Relationship Experienced by Tessa Young Shown in “After” Movie: A Content Analysis and Psychological Approach - Sutrisno, Bejo; Wilar, Debora Eunia; Sukrisno, Rachmawati (STIBA IEC JAKARTA, 2024)
This study is attempt to analyze the toxic relationship that the main character, Tessa Young, experienced in the ‘After’ Movie, which was released in 2019. It is about the main character who experienced multiple effects of toxic relationship. The aims of this study are to analyze and explain what the characteristics and negative effects of toxic relationship experienced by Tessa Young. This study uses qualitative method that includes content analysis and psychological approach. The data in this study was gathered from both primary and secondary sources. The primary data is the script of the movie and the secondari data are textbooks, articles, and journals. The findings of this study are that toxic relationship are dangerous and should be avoided by a couple. It brings negative impacts for couples that can change someone’s habit for doing bad things. The characteristics and negative effects of toxic relationships can help female friends out there to fight against toxic relationships.